KINERJA RANTAI NILAI KEDELAI DI KABUPATEN GROBOGAN - Budiraharjo, Kustopo; Nurfadillah, Suryani; Roessali, Wiludjeng (Jurnal AGRISEP, 2020)
This study aims to evaluate the performance of the soybean value chain in Grobogan Regency, Central Java. Different from other studies, this study portrayed the performance of the soybean value chain as a whole through a systems approach. The method used in this research is survey. This study used observation and structured interviews to farmers, marketing institutions, and other stakeholders to obtain primary data. A total of 65 soybean farmers from 6 districts in Grobogan Regency were selected by proportional random sampling to be used as a respondent. Determination of respondents for marketing to consumers using snowball sampling. This study uses descriptive-quantitative analysis methods with Value Chain Analysis (VCA), farm income, and marketing margins. The main activities in the soybean value chain consist of inbound logistics, operations, outbound logistics, marketing, and services. The logistical aspect performance is constrained by the incompatibility of the use of inputs with the standard. The performance aspect of operations is reflected by the productivity and income of farmers, amounting to 1,822 kg/ha and Rp. 1,728,320 / ha. Outgoing logistics related to farmers' dependence on collecting traders. The performance of marketing aspects is reflected in channel margins 1, 2, and 3, namely Rp. 750 / kg, Rp. 1,350 / kg, and Rp. 1,475 / kg. The most dominant service aspect is the role of RKG. Supporting performance aspects need to be improved by improving infrastructure, adopting technology, and improving farmer card implementation.